Particles, forces and the early universe - Risto Raitio (Nuclear Physics B, 2025)
This article reveals the unexpected result that three a priori distinct ideas—global supersymmetry of preons, Hartle-Hawking cosmology, and Chern-Simons quantum gravity—share common concepts that offer paths beyond the Standard Model. Differences from the MSSM are discussed.